Exploring the alterations and function of skin microbiome mediated by ionizing radiation injury - Huang, Biao; An, Lu; Su, Wenxing; Yan, Tao; Zhang, Haifang; Yu, Dao-Jiang (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Radiation-induced skin injury (RISI) is still the most common adverse side effect during radiotherapy. The role of skin microbial barrier in the pathogenesis and progress of RISI needs to be fully studied. Methods: To explore the alterations and function of skin microbiota in RISI. Unculturable approach was applied to characterize cutaneous microbiomes of radiation-induced animal model by sequencing V1‑V3 regions of 16S rRNA gene. Combined with the downloaded clinical patient data, comprehensive analysis was performed to identify potential radioprotective species and metabolic pathways. Results: There was no significant difference in alpha diversity index (sobs, Shannon, Simpson, ace, chao) between acute radiation injury and control group. Phylum level analyses of RISI microbiomes exhibited alternately significant predominance of Firmicutes (Mean abundance: 67%, Corrected Pvalue=0.0035). Among them, Streptococcus, Staphylococcus, Acetivibrio ethanolgignens group, Peptostreptococcus, Anaerofilum and UCG-002 (LDA>3, P<0.05) were identified as the core genus of Firmicutes. In addition, Lachnosiraceae and Lactobacillus occupied important positions in their interaction network (correlation>0.6, Pvalue <0.05). The differential metabolic pathways of RISI were mainly associated with Carbohydrate metabolism (butanoate metabolism, propanoate metabolism), Amino acid metabolism (tryptophan metabolism, histidine metabolism), Energy metabolism, and Lipid metabolism (fatty acid degradation, fatty acid biosynthesis). Conclusion: Our study provides new insight about the potential mechanism and radioprotective species in RISI progressing. The overwhelming predominance of Firmicutes members such as Streptococcaceae, Staphylococcaceae, Lachnospiraceae and Lactobacillus is potentially related to prompt rapidly healed in RISI. The microbiota metabolite axis plays a critical role in radioprotection and provides promising therapeutic targets to treat the adverse side effects of RISI.